Molecular characterization of caspase-8-like and its expression induced by microcystin-LR in grass carp (Ctenopharygodon idella). Issue 89 (June 2019) - Wei, LiLi; He, Li; Fu, Jianping; Liu, Yi; Ruan, Jiming; Liu, Lin; Zhong, Qiwang
Abstract: Caspase-8, an initiator caspase, plays a vital role in apoptosis. In this study, caspase-8-like (named as Cicaspase-8-like), a homologue of caspase-8, was identified in grass carp ( Ctenopharygodon idella ). The full-length cDNA sequence of CiCaspase-8-like was 1409 bp and contained a 162 bp 5′-UTR, a 239 bp 3′-UTR and a 1008 bp coding sequence. The putative amino acids sequence was 335 residues long, including a large subunit (P20) and a small subunit (P10), but lacking conserved death effector domains. A histidine active site DHSQMDAFVCCVLSHG and a cysteine active-site motif KPKLFFIQACQG were found in P20. Phylogenetic analysis showed that Cicaspase-8-like clustered with the caspase-8 and caspase-8-like of other fish and grouped closely with Carassius auratus caspase-8-like. Quantitative real-time PCR revealed that the Cicaspase-8-like mRNA were expressed constitutively in all tested tissues from healthy grass carp, with high expression level in the blood, spleen, liver and gill, indicating its role in immune reaction. The expression of Cicaspase-8-like mRNA was decreased significantly in the liver because of the stress caused by microcystin-LR (MC-LR) (75 and 100 μg MC-LR/kg BW) at 24 h and 96 h post injection ( P < 0.05), but it was increased significantly in grass carp treated with 25 μg MC-LR/kg BW at 24 h ( P < 0.05) post injection. Cleaved fragments of Cicaspase-8-like were observed using western blot analysis, and the expression of Cicaspase-8-like protein was increased after MC-LR treatments. Moreover, the expression of both caspase-9 and caspase-3 mRNA increased significantly after treatment with the three doses of MC-LR. TUNEL assay results showed remarkable changes in apoptosis after the MC-LR treatment. These results suggest that Cicaspase-8-like is an important caspase and plays an essential role in MC-LR-induced apoptosis. Highlights: Caspase-8-like (Cicaspase-8-like) was cloned in grass carp, and expressed in all examined tissues. The expression of Cicaspase-8-like protein was up-regulated after MC-LR challenge. Caspase-9 and caspase-3 mRNA levels were increased significantly after MC-LR treatment. The apoptosis in the liver was induced by MC-LR. Our findings suggest the involvement of Cicaspase-8-like in MC-LR-induced apoptosis.